The effects of molar activity on [18F]FDOPA uptake in patients with neuroendocrine tumors - Gilles N. Stormezand; Romano S. B. H. Schreuder; Adrienne H. Brouwers; Riemer H. J. A. Slart; Philip H. Elsinga; Annemiek M. E. Walenkamp; R. A. J. O. Dierckx; Andor W. J. M. Glaudemans; Gert Luurtsema (EJNMMI Research, 2021)
Abstract Background 6-[18F]fluoro-l-3,4-dihydroxyphenyl alanine ([18F]FDOPA) is a commonly used PET tracer for the detection and staging of neuroendocrine tumors. In neuroendocrine tumors, [18F]FDOPA is decarboxylated to [18F]dopamine via the enzyme amino acid decarboxylase (AADC), leading to increased uptake when there is increased AADC activity. Recently, in our hospital, a new GMP compliant multi-dose production of [18F]FDOPA has been developed, [18F]FDOPA-H, resulting in a higher activity yield, improved molar activity and a lower administered mass than the conventional method ([18F]FDOPA-L). Aims This study aimed to investigate whether the difference in molar activity affects the [18F]FDOPA uptake at physiological sites and in tumor lesions, in patients with NET. It was anticipated that the specific uptake of [18F]FDOPA-H would be equal to or higher than [18F]FDOPA-L. Methods We retrospectively analyzed 49 patients with pathologically confirmed NETs and stable disease who underwent PET scanning using both [18F]FDOPA-H and [18F]FDOPA-L within a time span of 5 years. A total of 98 [18F]FDOPA scans (49 [18F]FDOPA-L and 49 [18F]FDOPA-H with average molar activities of 8 and 107 GBq/mmol) were analyzed. The SUVmean was calculated for physiological organ uptake and SUVmax for tumor lesions in both groups for comparison, and separately in subjects with low tumor load (1–2 lesions) and higher tumor load (3–10 lesions). Results Comparable or slightly higher uptake was demonstrated in various physiological uptake sites in subjects scanned with [18F]FDOPA-H compared to [18F]FDOPA-L, with large overlap being present in the interquartile ranges. Tumor uptake was slightly higher in the [18F]FDOPA-H group with 3–10 lesion (SUVmax 6.83 vs. 5.19, p < 0.001). In the other groups, no significant differences were seen between H and L. Conclusion [18F]FDOPA-H provides a higher activity yield, offering the possibility to scan more patients with one single production. Minor differences were observed in SUV’s, with slight increases in uptake of [18F]FDOPA-H in comparison to [18F]FDOPA-L. This finding is not a concern for clinical practice, but could be of importance when quantifying follow-up scans while introducing new production methods with a higher molar activity of [18F]FDOPA.